2016
DOI: 10.1007/s12011-016-0784-2
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Ameliorates Renal Oxidative Damage and Thyroid Dysfunction in Rats Chronically Exposed to Fluoride

Abstract: Excessive exposure to fluoride poses several detrimental effects to human health particularly the kidney which is a major organ involved in its elimination from the body. The influence of taurine on fluoride-induced renal toxicity was investigated in a co-exposure paradigm for 45 days using five groups of eight rats each. Group I rats received normal drinking water alone, group II rats were exposed to sodium fluoride (NaF) in drinking water at 15 mg/L alone, group III received taurine alone at a dose of 200 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The doses of DEN and fluoride used in this study were selected from our pilot studies and earlier published studies . The final body weights of the rats were taken before the collection of blood from retro‐orbital venous plexus into plain tubes and sacrifice by cervical dislocation on day 15.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The doses of DEN and fluoride used in this study were selected from our pilot studies and earlier published studies . The final body weights of the rats were taken before the collection of blood from retro‐orbital venous plexus into plain tubes and sacrifice by cervical dislocation on day 15.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, epidemiological studies have shown that people residing in some countries in Asia, Africa, and the Eastern Mediterranean could be exposed to polluted water having about 20 mg/L fluoride level . Hepatic and renal toxicities associated with long‐term exposure to fluoride have been linked to induction of oxidative stress and DNA damage in rodents …”
Section: Introductionmentioning
confidence: 99%
“…The doses of NaF and taurine used in the present study were selected based on the previously published data (Chattopadhyay et al 2011;Adedara et al 2017). Twenty-four hours after the last exposure, the final body weights of the rats were taken, blood collected from retro-orbital venous plexus using heparin containing tubes before they were sacrificed by cervical dislocation.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Taurine (2‐aminoethanesulfonic acid) is a sulfur‐amino acid that derives from cysteine that was first discovered in 1827 by German scientists Friedrich Tiedemann and Leopold Gmelin in ox bile ( Taurus in Latin) . A main constituent of human bile salts as well, it was later identified in 1846 by Ronalds; while the mechanisms are still incompletely understood, it has since been appreciated for its role as an antioxidant, osmoprotectant, modulator of mitochondrial calcium homeostasis, and neuroprotective agent . Taurine is a nonessential amino acid, the circulating levels of which are significantly impacted by dietary intake (the normal diet typically contains 40 to 400 mg per day).…”
mentioning
confidence: 99%